### 3/y-1=2/y-3

This solution deals with adding, subtracting và finding the least common multiple.

## Step by Step Solution

### Rearrange:

Rearrange the equation by subtracting what is khổng lồ the right of the equal sign from both sides of the equation : 3/y-1-(2/y-3)=0

## Step 1 :

2 Simplify — yEquation at the kết thúc of step 1 : 3 2 (— - 1) - (— - 3) = 0 y y

## Step 2 :

Rewriting the whole as an Equivalent Fraction :2.1Subtracting a whole from a fraction Rewrite the whole as a fraction using y as the denominator :

3 3 • y 3 = — = ————— 1 y Equivalent fraction : The fraction thus generated looks different but has the same value as the whole Common denominator : The equivalent fraction and the other fraction involved in the calculation share the same denominator

Adding fractions that have a common denominator :2.2 Adding up the two equivalent fractions add the two equivalent fractions which now have a common denominatorCombine the numerators together, put the sum or difference over the common denominator then reduce to lớn lowest terms if possible:

2 - (3 • y) 2 - 3y ——————————— = —————— y y Equation at the kết thúc of step 2 : 3 (2 - 3y) (— - 1) - ———————— = 0 y y

## Step 3 :

3 Simplify — yEquation at the kết thúc of step 3 : 3 (2 - 3y) (— - 1) - ———————— = 0 y y

## Step 4 :

Rewriting the whole as an Equivalent Fraction :4.1Subtracting a whole from a fraction Rewrite the whole as a fraction using y as the denominator :

1 1 • y 1 = — = ————— 1 y Adding fractions that have a common denominator :4.2 Adding up the two equivalent fractions

3 - (y) 3 - y ——————— = ————— y y Equation at the kết thúc of step 4 : (3 - y) (2 - 3y) ——————— - ———————— = 0 y y

## Step 5 :

Adding fractions which have a common denominator :5.1 Adding fractions which have a common denominatorCombine the numerators together, put the sum or difference over the common denominator then reduce lớn lowest terms if possible:

(3-y) - ((2-3y)) 2y + 1 ———————————————— = —————— y y Equation at the end of step 5 : 2y + 1 —————— = 0 y

## Step 6 :

When a fraction equals zero :6.1 When a fraction equals zero ...Where a fraction equals zero, its numerator, the part which is above the fraction line, must equal zero.Now,to get rid of the denominator, Tiger multiplys both sides of the equation by the denominator.Here"s how:

2y+1 ———— • y = 0 • y y Now, on the left hand side, the y cancels out the denominator, while, on the right hand side, zero times anything is still zero.The equation now takes the shape:2y+1=0

Solving a Single Variable Equation:6.2Solve:2y+1 = 0Subtract 1 from both sides of the equation:2y = -1 Divide both sides of the equation by 2:y = -1/2 = -0.500